Montenegro : Technical Assistance Report-Report on External Sector Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2018)
To support the compilation of external sector statistics (ESS) in Montenegro, the International Monetary Fund (IMF)'s Statistics Department (STA) conducted a technical assistance (TA) mission during December 4-15, 2017. The mission was requested by the Central Bank of Montenegro (CBM), the main ESS compiling agency, and supported by the IMF's European Department. STA's mission for the Enhanced General Data Dissemination System (e-GDDS) during June 28-July 4, 2017 also suggested TA for Montenegro to start compiling international investment position (IIP) and external debt statistics (EDS). The mission focused on assisting the CBM in preparing IIP, EDS, Reserves Data Template (RDT), and addressing persistent net errors and omissions. Compilation of IIP and EDS is required to be qualified for Threshold 2 of the e-GDDS. Montenegro does not participate in the Eurosystem, but it is fully eurorized. Euro circulating in Montenegro should be included in the assets of the IIP for Montenegro, but difficulty in estimating the amount had been preventing the CBM from compiling IIP for several years.